2002
DOI: 10.1093/bioinformatics/18.8.1046
|View full text |Cite
|
Sign up to set email alerts
|

Computational identification of putative programmed translational frameshift sites

Abstract: Complete results from the analysis of S. cerevisiae are available on http://www.gesteland.genetics.utah.edu/freqAnalysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 22 publications
0
61
0
Order By: Relevance
“…3A), the sequence CTTAGGC is a slippery sequence that can promote z40% frameshift efficiency (Belcourt and Farabaugh 1990;Shah et al 2002;Farabaugh et al 2006). On the 0-frame, CTT-AGG is translated as Leu-Arg.…”
Section: Ser1mentioning
confidence: 99%
See 1 more Smart Citation
“…3A), the sequence CTTAGGC is a slippery sequence that can promote z40% frameshift efficiency (Belcourt and Farabaugh 1990;Shah et al 2002;Farabaugh et al 2006). On the 0-frame, CTT-AGG is translated as Leu-Arg.…”
Section: Ser1mentioning
confidence: 99%
“…In addition, it will be of value to test this strain under various stress conditions, including nutrient deprivation, response to reactive oxygen species, and chemicals, to observe other phenotypes related to ABP140. Another intriguing feature of ABP140/TRM140 is the presence of an internal frameshift site (Asakura et al 1998) at which the slippery sequence, CUUAGGC, can promote a 40% frameshift frequency (Belcourt and Farabaugh 1990;Shah et al 2002;Farabaugh et al 2006). This sequence was first identified as the +1 frameshift site of the TYB gene of the Ty1 retrotransposon (Kawakami et al 1993;Voytas and Boeke 1993).…”
Section: Ser1mentioning
confidence: 99%
“…Consequently, one might expect shift-prone sequences to be selected against and therefore underrepresented in coding sequences, especially those of highly expressed genes. Conversely, when shiftprone sequences occur, analysis for their possible utilization in gene expression is merited (25,52). …”
mentioning
confidence: 99%
“…Experimental results of testing FSFinder2 on ~190 genomic and partial DNA sequences showed that it predicted frameshift sites efficiently and with greater sensitivity and specificity than other programs, because it focused on the overlapping regions of ORFs and prioritized candidate signals (For -1 frameshifts, sensitivity was 0.88 and specificity 0.97; for +1 frameshifts, sensitivity was 0.91 and specificity 0.94) [6,[9][10][11]. FSFinder2 has been successfully used to find unknown frameshift sites in the Shewanella genome.…”
Section: Resultsmentioning
confidence: 99%